Knowledge and attitude towards human papillomavirus and its vaccination among medical students: a cross sectional study - Thakur, Mamta; Khanam, Najnin; Yadav, Rajendra; Soni, Gopal P.; Kamble, Nitin (International Journal Of Community Medicine And Public Health, 2023)
Background: One of the causes of penile cancer in men and cervical cancer in women is infection with the human papillomavirus (HPV). An efficient way to prevent high risk HPV infection is by HPV vaccination. This study was conducted to assess knowledge and attitude towards human papillomavirus and its vaccination. Methods: The cross-sectional study was done among under graduate medical students. Total 428 students were voluntarily participated. Dichotomous (yes/no) items used to assess knowledge of the students towards human papillomavirus and its vaccination. The 3-point Likert scale (agree, uncertain, disagree) used to assess attitude towards HPV vaccination. Results: Most 71.49% of them knew that HPV infection may leads to carcinoma cervix whereas only 29.44% knew that HPV infection may leads to penile cancer. Most 76.63% of them agreed to recommend HPV vaccine for adolescent girls whereas only 36.68% agreed to recommend HPV vaccine for adolescent boys. Conclusions: According to the study, college students had knowledge towards HPV vaccination despite acceptance of HPV vaccination among students were very less. Medical students, can play a big role in giving advice on how to prevent HPV-related penile and cervical cancer.